Maths, arts, or language? / Dr. Leow Min Hui - Leow, Min Hui (Academy of Language Studies, 2024)
Language learning is a continuous active learning process throughout one’s life. Humans learn language to communicate their feelings, thoughts, and establish relationships with others. Therefore, active learning in a language classroom is an essential approach in which active interaction using target language comes naturally. Active learning is commonly viewed as a superior teaching and learning approach in the 21st century classroom (Bolefski, 2020; Yuh,2020). Active learning in a language classroom allows students to engage in multi-sensory learning via speaking, listening, and reading at the same time. Students’ engagement in active learning activities throughout the multi-sensory learning circumstance makes learning more fun and productive. In a tertiary foreign language education, the main goal is to help students acquire practical communication skills that will aid them to analyse information, convey ideas, and use the target language in daily life. Therefore, it is important to link language to different contexts or subjects in order to ensure the functional purpose of the target language. Consequently, this type of multidisciplinary integrated language classroom transforms the learning environment from passive to active as students become the centre of the learning experience by collaborating on target language in real-life or career contexts that relate to their future pursuits.